Abnormalities in the vagus nerve in canine acrylamide neuropathy. - Satchell, P M (1982)
Dogs exposed to acrylamide develop a sensorimotor peripheral neuropathy and megaoesophagus. The presence of neuropathy was confirmed electrophysiologically and histologically. Hindlimb motor conduction velocity was reduced and there was a loss of large diameter myelinated fibres in the dorsal common digital nerve and the tibial nerve. The conduction velocity of vagal motor fibres innervating the thoracic oesophagus was not decreased; there was a reduction in the conduction velocity of the mixed nerve action potential of the vagus. Degenerating nerve fibres were observed in the vagus in the midthoracic region. The damage to vagal nerve fibres may be an important factor in the causation of megaoesophagus.